Foods and supplements as probiotic delivery vehicles - Pimentel, Tatiana Colombo; da Costa, Whyara Karoline Almeida; Tammy Priscilla Chioda, Delfino [UNESP]; Sônia Mariza Luiz, de Oliveira; Katia, Sivieri [UNESP]; Marciane, Magnani (Elsevier, 2022)
This chapter aimed to discuss the effect of probiotics (foods and supplements) on human health. Lactiplantibacillus, Limosilactobacillus, Lacticaseibacillus, Ligilactobacillus, and Bifidobacteria are the most common probiotic strains used. Probiotic foods comprised mainly yogurt, fermented milk, and kefir. The advantages of probiotic foods are the lower cost, positive consumer attitude, possible synergistic effects between the ingredients and probiotics, and the high variation potential. Probiotic foods consumption may improve the constipation symptoms, bone health markers, lipid profile, body mass, blood pressure, and postprandial glycemia. On the other hand, supplements can transfer high numbers of viable probiotics into the gastrointestinal tract without considerable loss during processing and storage and have lower difficulties from regulatory administration and legislation standpoint. Probiotic supplements may relieve intestinal disease symptoms, improve depression scores and oral health, and alleviate atopic dermatitis and urogenital disease. Overall, probiotic foods may be recommended for general use and supplements for specific therapeutic applications.
Keywords: Bifidobacteria; Dairy foods; Food supplements; Functional food; Health benefits; Lactobacillus; Probiotic; Probiotic carrier